Genetic overlap between sarcoidosis and lung cancer: a combined in silico and in vitro approach - Sanjukta Dasgupta; Moupiya Ghosh; Subhendu Chakrabarty; Gopal Chakrabarti; Amlan Das (Hereditas)
Abstract Sarcoidosis patients exhibit an elevated risk of developing lung cancer (LC), suggesting shared genetic and molecular mechanisms between these conditions. This study aimed to identify common differentially expressed genes (DEGs) in sarcoidosis and LC and to evaluate the therapeutic potential of a repurposable drug targeting these shared genes. Gene expression datasets (GSE157671 and GSE229253) were analyzed to identify overlapping DEGs, with validation performed using additional GEO datasets and the GEPIA tool. Functional enrichment and protein–protein interaction (PPI) analyses were conducted using Enrichr and STRING, while associated miRNAs and transcription factors were identified via miRNet. Twelve DEGs—SALL4, WNT10A, RASAL1, CAMK2B, GADD45B, KLF4, OLR1, CSF3, WIF1, RAMP3, AGER, and PRKAG3—were consistently dysregulated in both diseases. These genes were significantly associated with epithelial cell enrichment and the Wnt signaling pathway. Drug–gene interaction analysis using DGIdb prioritized metformin as a candidate drug targeting PRKAG3. Its structural integrity was confirmed via X-ray diffraction (XRD) and Rietveld refinement. In vitro validation using MTT assays revealed that metformin selectively reduced viability in A549 (adenocarcinoma human alveolar basal epithelial cells) and HeLa (a widely used epithelial cancer cell line), with minimal cytotoxicity in WI38 normal lung fibroblasts. Colony formation assays further demonstrated dose-dependent, long-term growth inhibition in cancer cells, corroborated by observable morphological alterations. Overall, this study highlights shared pathogenic signatures between sarcoidosis and LC and proposes metformin as a promising therapeutic candidate. These findings support the rationale for drug repurposing and the development of targeted therapies for patients with overlapping disease profiles or those at increased risk of LC progression from sarcoidosis.